Substance and Accidence: Imago, Vestigium, and Relatio in Ockham’s Philosophy and Theology - LI, Yang (Journal of Research for Christianity in China (JRCC), 2025)
In his Scriptum in Librum Primum Sententiarum, Ockham discusses the differing roles of traces and images in guiding human understanding of the Trinity. As a scholar of nominalist stance, Ockham argues that traces possess a certain empirical quality, thus granting them reality. Traces logically represent the real distinctions within the Trinity, while images, based on some productive principle, only have conceptual similarity or representation, and therefore lack reality and real distinction. However, to ensure the accuracy of theological doctrine, Ockham treats images as the concretization of concepts, thus giving images a representational capacity with substantiality. Although this conceptual concretization contradicts Ockham’s nominalist philosophy, it guarantees the correctness of theological teachings. This internal tension is also reflected in Ockham’s discussions on issues like “relatio” (as a category) and the dual nature of Christ. Despite Ockham’s view of relation as an accident and his demonstration of the absurd logical conclusions resulting from considering relations as substances, in order to preserve the real existence of the Trinity, the relationships among the Father, the Son, and the Holy Spirit must necessarily be regarded as real items. In fact, Ockham’s divergent approaches to the same issue from theological and philosophical perspectives reveal the tension between faith and reason in the Middle Ages—a dynamic interplay that medieval philosophers collectively sought to confront and reconcile.